2015
DOI: 10.1111/liv.12984
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic factors in patients with hepatocellular carcinoma and iron overload – a prospective series of 234 patients

Abstract: Additional genetic risk factors of IO were found in 18 patients (7.7%) among a large series of 234 HCC patients. Screening for IO and the associated at-risk genotypes in patients who have developed HCC, is useful for both determining etiologic diagnosis and enabling family screening and possibly primary prevention in relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The normal expression of SLC40A1 is essential to iron metabolism homeostasis. Moreover, many precious articles have revealed that abnormal iron metabolism induced by SLC40A1 mutation or intron sequence polymorphism is associated with autosomal dominant hemochromatosis, inflammatory reaction, and occurrence of liver cancer [ 17 22 ]. Our precious microarray data revealed that SLC40A1 was a potential downstream gene of Nrf2 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The normal expression of SLC40A1 is essential to iron metabolism homeostasis. Moreover, many precious articles have revealed that abnormal iron metabolism induced by SLC40A1 mutation or intron sequence polymorphism is associated with autosomal dominant hemochromatosis, inflammatory reaction, and occurrence of liver cancer [ 17 22 ]. Our precious microarray data revealed that SLC40A1 was a potential downstream gene of Nrf2 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was a retrospective, single center study, and there was no information about the HH‐associated mutation profiles or blood iron levels of the subject patients. Our previous studies on the prevalence of the C282Y or S65C HFE mutation was 0% and only 8.5% for H63D heterozygotes in a Korean population; however, the mutation rates of the HFE ‐form or non‐ HFE ‐form of HH were not evaluated in this study; these could be genetic risk factors for iron overload among the HCC patients . Serum iron markers such as ferritin and transferrin or iron‐regulatory hormone hepcidin were also not examined in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous studies on the prevalence of the C282Y or S65C HFE mutation was 0% and only 8.5% for H63D heterozygotes in a Korean population; 12 however, the mutation rates of the HFE-form or non-HFE-form of HH were not evaluated in this study; these could be genetic risk factors for iron overload among the HCC patients. 33 Serum iron markers such as ferritin and transferrin or iron-regulatory hormone hepcidin were also not examined in this study. Nevertheless, this study has several strong points such as a relatively homogenous patient population consisting of curatively resected HCC patients, iron evaluation using surgical specimens with a sufficient tissue size, use of two different iron scoring methods, and a long follow-up of the subjects reliably showing the survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that patients with iron overload are at increased risk for HCC development. 22 In the presence of iron overload, iron staining reveals an extensive deposition of iron within cells of the non-tumour liver parenchyma, but no iron in the tumour tissue. 23 These results suggest that neoplastic hepatocytes have the potential to avoid excess iron accumulation in their cytoplasm for the purpose of cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that patients with iron overload are at increased risk for HCC development . In the presence of iron overload, iron staining reveals an extensive deposition of iron within cells of the non‐tumour liver parenchyma, but no iron in the tumour tissue .…”
Section: Discussionmentioning
confidence: 99%